The role of calcium crystals and their effect on osteoarthritis pathogenesis. Issue 4 (December 2021) - Stücker, Sina; Bollmann, Miriam; Garbers, Christoph; Bertrand, Jessica
Abstract: Osteoarthritis (OA) is a degenerative joint disease characterized by progressive degeneration of articular cartilage. Due to its high prevalence and limited treatment options, OA has become one of the most disabling diseases in developed countries. In recent years, OA has been recognized as a heterogenic disease with various phenotypes. Calcium crystal-related endotypes, which are defined by either a distinct functional or pathobiological mechanism, are present in approximately 60% of all OA patients. Two different calcium crystals can accumulate in the joint and thereby calcify the cartilage matrix, which are basic calcium phosphate (BCP) and calcium pyrophosphate (CPP) crystals. The formation of these crystals depends mainly on the balance of phosphate and pyrophosphate, which is regulated by specific proteins controlling the pyrophosphate metabolism. Dysregulation of these molecules subsequently leads to preferential formation of either BCP or CPP crystals. BCP crystals, on the one hand, are directly associated with OA severity and cartilage degradation. They are mostly located in the deeper cartilage layers and are associated with chondrocyte hypertrophy. CPP crystal deposition, on the other hand, is a hallmark of chondrocalcinosis and is associated with aging and chondrocyte senescence. Therefore, BCP and CPP crystals are associated with different chondrocyte phenotypes. However, BCP and CPP crystals are not mutually exclusive and can coexist in OA, creating a mixed endotype of OA. Both crystals clearly play a role in the pathogenesis of OA. However, the exact impact of each crystal type on either driving the disease progression or being a result of chondrocyte differentiation is still to be elucidated.